All-solid battery and manufacturing method thereof
Patent Information
- Application Number
- JP2024104425
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-21
- Filing Date
- 2024-06-27
- Publication Date
- 2025-03-06
AI Technical Summary
【0009】 本発明の全固体電池は、固体電解質層を各電極に直接的に形成することによって、各電極と固体電解質層の安定的な結合により電極と固体電解質層の物理的脱離を防止することができ、優れた機械的強度を有した固体電解質層を具現することができる。
Smart Images

Figure 2025029575000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state battery having a structure in which different types of sulfide-based solid electrolyte layers are in face-to-face contact with each other, and a method for manufacturing the same. [Background technology]
[0002] Currently, unprecedented climate change is occurring all over the world, and efforts are being made in each country to achieve carbon neutrality in order to solve these environmental problems. Carbon neutrality means minimizing greenhouse gas emissions and absorbing the emitted greenhouse gases in various ways to effectively reduce greenhouse gas emissions to zero (0). This ultimately leads to a movement to curb the use of fossil fuels and expand the use of new renewable energy. Energy storage is essential to utilize new renewable energy, and batteries can be used as the main means of energy storage. In the case of automobile production, there is also a movement to reduce the use of internal combustion engines that use existing fossil fuels and expand the use of battery-powered electric vehicles (EVs).
[0003] Electric vehicles generally use lithium secondary batteries with high energy density, but lithium secondary batteries using liquid organic electrolytes have a problem of high risk of fire due to heat accumulation inside the battery when operated at high temperatures. Therefore, as an alternative to conventional lithium secondary batteries using liquid organic electrolytes, active research and development has been conducted on all-solid-state batteries that use solid electrolytes to prevent electrolyte leakage and significantly reduce the risk of fire and explosion.
[0004] As the solid electrolyte, materials such as polymer-based solid electrolyte, oxide-based solid electrolyte, and sulfide-based solid electrolyte are generally used. Among them, polymer-based solid electrolytes are widely used due to their advantages such as low price, flexibility of materials, easy processability, battery stability, and improved energy density due to thinning of electrolyte layers and batteries, but have a problem of being damaged during the manufacturing process of batteries due to their weak strength. Therefore, a technology has been proposed in which a solid electrolyte membrane is manufactured by mixing a porous polymer support and a solid electrolyte to improve its mechanical strength, but the large resistance of the porous polymer support not only causes deterioration of the performance of the all-solid-state battery, but also reduces the efficiency of the manufacturing process of forming a composite of the porous polymer support and the solid electrolyte, which remain issues to be solved.
[0005] Therefore, there is a need to develop a technology that can improve the process efficiency of all-solid-state batteries while maintaining the excellent performance of the all-solid-state batteries. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention is intended to solve the above-mentioned problems, and aims to provide an all-solid-state battery and a manufacturing method thereof, which can stably form a solid electrolyte layer on each electrode to prevent physical detachment of the electrode and the solid electrolyte layer, as well as form a solid electrolyte layer with excellent mechanical strength, and form different solid electrolyte layers on each electrode and bring them into face-to-face contact with each other, thereby ensuring electrochemical stability at the electrode-solid electrolyte layer interface. [Means for solving the problem]
[0007] According to one embodiment of the present invention, there is provided an all-solid-state battery including: a positive electrode laminate part including a positive electrode and a first external solid electrolyte layer formed on at least one surface of the positive electrode; and a negative electrode laminate part including a negative electrode and a second external solid electrolyte layer formed on at least one surface of the negative electrode; wherein the first external solid electrolyte layer of the positive electrode laminate part and the second external solid electrolyte layer of the negative electrode laminate part face to face and are in contact with each other, and the first external solid electrolyte layer and the second external solid electrolyte layer include sulfide-based solid electrolytes having different chemical compositions.
[0008] In addition, according to another embodiment of the present invention, there is provided a method for manufacturing an all-solid-state battery, the method including: forming a positive electrode laminate part having a first external solid electrolyte layer disposed on at least one surface of a positive electrode; forming a negative electrode laminate part having a second external solid electrolyte layer disposed on at least one surface of a negative electrode; and contacting and rolling the first external solid electrolyte layer of the positive electrode laminate part and the second external solid electrolyte layer of the negative electrode laminate part so as to face each other; wherein the first external solid electrolyte layer and the second external solid electrolyte layer include sulfide-based solid electrolytes having different chemical compositions. Effect of the Invention
[0009] In the all-solid-state battery of the present invention, a solid electrolyte layer is directly formed on each electrode, and thus physical detachment between the electrode and the solid electrolyte layer can be prevented due to stable bonding between the electrode and the solid electrolyte layer, thereby realizing a solid electrolyte layer having excellent mechanical strength.
[0010] Furthermore, according to the method for producing an all-solid-state battery of the present invention, by forming different solid electrolyte layers on the electrodes and bringing them into contact with each other so as to face each other, it is possible to ensure electrochemical stability at the electrode-solid electrolyte layer interface and produce an all-solid-state battery with improved performance with high efficiency. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic diagram illustrating a manufacturing process of an all-solid-state battery according to an embodiment of the present invention. [Diagram 2]1 is a flowchart showing a method for manufacturing an all-solid-state battery according to an embodiment of the present invention. [Diagram 3] 1 is a diagram showing charge / discharge profiles for all-solid-state batteries according to Example 1 and Comparative Examples 1 to 3. [Figure 4] 1 is a graph showing a change in capacity with the progress of cycles for all-solid-state batteries according to Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the all-solid-state battery and the manufacturing method thereof will be described in detail so that a person having ordinary skill in the art to which the present invention pertains can easily carry out the present invention.
[0013] An all-solid-state battery according to an embodiment of the present invention includes a positive electrode laminate unit including a positive electrode and a first external solid electrolyte layer formed on at least one surface of the positive electrode; and a negative electrode laminate unit including a negative electrode and a second external solid electrolyte layer formed on at least one surface of the negative electrode. The first external solid electrolyte layer of the positive electrode laminate unit and the second external solid electrolyte layer of the negative electrode laminate unit face each other and are in contact with each other, and the first external solid electrolyte layer and the second external solid electrolyte layer include sulfide-based solid electrolytes having different chemical compositions.
[0014] The first external solid electrolyte layer of the positive electrode lamination part and the second external solid electrolyte layer of the negative electrode lamination part may be in contact with each other so as not to be physically separated (detached). That is, after separately manufacturing a positive electrode having a first external solid electrolyte layer formed thereon and a negative electrode having a second external solid electrolyte layer formed thereon, the first external solid electrolyte layer and the second external solid electrolyte layer are brought into contact with each other so as to face each other, so that the positive electrode or the negative electrode and the first external solid electrolyte layer and the second external solid electrolyte layer formed on one surface thereof may be bonded to each other while maintaining their independent shapes and components without being mixed with each other and while not being physically separated (detached) from each other and maintaining a sufficient bonding strength.
[0015] The sulfide-based solid electrolyte may include a compound having an agyrodite crystal structure, and in particular, the lithium ion conductivity may be maximized by maximizing the substitution rate of Group 17 elements at the 4a and 4c sites in the agyrodite crystal structure.
[0016] The positive electrode may include a positive electrode active material and a first inner solid electrolyte.
[0017] The first internal solid electrolyte and the first external solid electrolyte may each independently include a compound represented by Chemical Formula 1 below. [ka] (In the above Chemical Formula 1, M 1 is at least one selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and mixtures thereof; M 2 is at least one selected from the group consisting of P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi, and mixtures thereof; M 3 is S, O or a mixture thereof, X is one or more elements selected from the group 17 elements; -1≦a<0.3, -0.2≦b≦0.)
[0018] Meanwhile, the positive electrode active material may include a compound represented by the following Chemical Formula 2: [ka] (In the above Chemical Formula 2, -0.05≦c≦0.2, 2≦d≦2.02; 0≦x≦1, 0≦y≦0.5, 0≦z≦0.5, and x+y+z=1; M 4 , M 5 and M 6is at least one selected from the group consisting of Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga, and B.
[0019] The positive electrode may be prepared by coating a positive electrode slurry including a positive electrode active material, a first internal solid electrolyte, a binder, a conductive material, a dispersant, and a solvent on a positive electrode current collector.
[0020] The binder may include, for example, one or more selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and copolymers thereof.
[0021] The conductive material may be graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives; but is not necessarily limited to these, and any material that has conductivity without inducing a chemical change in the battery can be used.
[0022] The dispersant may be a water-based dispersant or an organic dispersant such as N-methyl-2-pyrrolidone (NMP).
[0023] The solvent may be, for example, one selected from the group consisting of toluene, xylene, naphtha, benzene, chlorobenzene, and mixed solvents thereof, but is not necessarily limited thereto.
[0024] The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc.
[0025] The negative electrode may include a negative electrode active material and a second internal solid electrolyte.
[0026] The second internal solid electrolyte and the second external solid electrolyte may each independently contain a compound represented by the following Chemical Formula 3.
Chemical Formula
[0027] On the other hand, the negative electrode active material may include at least one selected from the group consisting of SiO a1 (0 < a1 ≦ 2), SiC a2 (0 < a2 ≦ 2), lithium-containing titanium composite oxide (LTO), artificial graphite, and natural graphite.
[0028] The lithium-containing titanium composite oxide is Li 4 Ti 5 O 12 、Li 0.8 Ti 2.2 O 4, Li 8 Ti 4 O 12 and LiTi 2 O 4 The present invention may include at least one selected from the group consisting of:
[0029] The negative electrode may be prepared by coating a negative electrode slurry, which includes a negative electrode active material, a second internal solid electrolyte, a binder, a conductive material, a dispersant, and a solvent, on a negative electrode current collector.
[0030] The binder, conductive material, dispersant, and solvent may be the same as those described for the positive electrode.
[0031] The negative electrode current collector may be made of, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like, or an aluminum-cadmium alloy.
[0032] The all-solid-state battery according to the present invention includes a cathode lamination part in which a first external solid electrolyte layer is formed on at least one surface of a cathode and an anode lamination part in which a second external solid electrolyte layer is formed on at least one surface of a cathode, which are manufactured independently, and thus physical detachment between each electrode and each external solid electrolyte layer can be suppressed despite volume changes of the electrodes that occur during external impact or charge / discharge, as compared to a case in which an electrode-solid electrolyte layer-electrode are sequentially laminated and rolled. Specifically, when the first external solid electrolyte layer is formed on the cathode and the second external solid electrolyte layer is formed on the anode, the cathode slurry and the anode slurry are adhered to the cathode and the anode, respectively, via a binder during drying, thereby preventing physical detachment.
[0033] In addition, the first external solid electrolyte layer of the positive electrode lamination part and the second external solid electrolyte layer of the negative electrode lamination part face each other while forming a thin-film layer structure including a sulfide-based solid electrolyte having a different chemical composition, and are in contact with each other. Therefore, even after rolling, the components of the solid electrolyte layers having different chemical compositions are not mixed with each other, and each can maintain its own independent chemical composition, as compared with the case where a solid electrolyte in a slurry state is applied to each electrode and rolled. More specifically, the first external solid electrolyte layer of the positive electrode lamination part in the present invention includes a sulfide-based solid electrolyte that is stable in a positive electrode operating voltage range of about 2.5 to 4.3 V, and the second external solid electrolyte layer of the negative electrode lamination part includes a sulfide-based solid electrolyte that is stable in a negative electrode operating voltage range of about 0 to 1.0 V, thereby improving the stability at the interfaces between the positive electrode and the negative electrode, suppressing side reactions at each interface, and effectively reducing ion transfer resistance. Meanwhile, when one type of solid electrolyte is applied between the positive and negative electrodes and rolled as in the conventional technology, the stability of the solid electrolyte is required in a wide voltage range from about 0 to 4.5 V. However, it is very difficult for a sulfide-based solid electrolyte to maintain stability in the above voltage range, and side reactions are likely to occur at the electrode interface, which leads to a problem of reduced performance of the all-solid-state battery.
[0034] A method for manufacturing an all-solid-state battery according to another embodiment of the present invention includes the steps of: forming a positive electrode laminate part having a first external solid electrolyte layer disposed on at least one surface of a positive electrode; forming a negative electrode laminate part having a second external solid electrolyte layer disposed on at least one surface of a negative electrode; and contacting and rolling the first external solid electrolyte layer of the positive electrode laminate part and the second external solid electrolyte layer of the negative electrode laminate part so as to face each other; wherein the first external solid electrolyte layer and the second external solid electrolyte layer include sulfide-based solid electrolytes having different chemical compositions.
[0035] First, a positive electrode lamination part is formed in which a first outer solid electrolyte layer is disposed on at least one surface of a positive electrode.
[0036] The positive electrode may include a positive electrode active material and a first inner solid electrolyte.
[0037] The first internal solid electrolyte and the first external solid electrolyte may each independently include a compound represented by Chemical Formula 1 below. [ka] (In the above Chemical Formula 1, M 1 is at least one selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and mixtures thereof; M 2 is at least one selected from the group consisting of P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi, and mixtures thereof; M 3 is S, O or a mixture thereof, X is one or more elements selected from the group 17 elements; -1≦a<0.3, -0.2≦b≦0.)
[0038] The positive electrode active material may include a compound represented by the following Chemical Formula 2: [ka] (In the above Chemical Formula 2, -0.05≦c≦0.2, 2≦d≦2.02; 0≦x≦1, 0≦y≦0.5, 0≦z≦0.5, and x+y+z=1; M 4 , M 5 and M 6 is at least one selected from the group consisting of Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga, and B.
[0039] The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode slurry including a positive electrode active material, a first internal solid electrolyte, a binder, a conductive material, a dispersant, a solvent, etc. Specifically, the positive electrode active material, the first internal solid electrolyte, the binder, the conductive material, and the dispersant are dispersed in a solvent to prepare a positive electrode forming slurry, which is then applied onto a positive electrode current collector and dried to prepare the positive electrode.
[0040] The binder may include, for example, one or more selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and copolymers thereof.
[0041] The conductive material may be graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives; but is not necessarily limited to these, and any material that has conductivity without inducing a chemical change in the battery can be used.
[0042] The dispersant may be a water-based dispersant or an organic dispersant such as N-methyl-2-pyrrolidone (NMP).
[0043] The solvent may be, for example, one selected from the group consisting of toluene, xylene, naphtha, benzene, chlorobenzene, and mixed solvents thereof, but is not necessarily limited thereto.
[0044] The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like.
[0045] The slurry may be applied by a known application method such as slot die coating, doctor blade method, dip method, reverse roll method, direct roll method, gravure method, extrusion method, or brush coating.
[0046] The drying may be performed by natural drying, hot air drying, cold air drying, air blowing, heat drying, or the like in order to volatilize the solvent, but is not necessarily limited to these. Any method can be used as long as it can evaporate the solvent in the slurry to produce a positive electrode in a solidified state.
[0047] The drying may be carried out at a temperature of from 50°C to 150°C.
[0048] The step of forming the positive electrode laminate part may include a step of coating a slurry for forming a first external solid electrolyte layer, the slurry including a first external solid electrolyte, a binder, and a dispersant, on at least one surface of the positive electrode, and drying the slurry. Specifically, the first external solid electrolyte, the binder, and the dispersant may be dispersed in a solvent to prepare a slurry for forming the positive electrode laminate part, and the slurry may be coated on at least one surface of the positive electrode, and dried.
[0049] The binder, dispersant, and solvent may be the same as those described in the method for manufacturing a positive electrode.
[0050] The method for applying the first outer solid electrolyte layer forming slurry to at least one surface of the positive electrode is not particularly limited, and the same method as the method for applying the positive electrode forming slurry onto the positive electrode current collector may be used.
[0051] The drying method and conditions for the production of the positive electrode laminate may be the same as those for the production of the positive electrode.
[0052] Next, a step of forming a negative electrode laminate portion in which a second external solid electrolyte layer is disposed on at least one surface of the negative electrode is performed.
[0053] The negative electrode may include a negative electrode active material and a second internal solid electrolyte.
[0054] The second internal solid electrolyte and the second external solid electrolyte may each independently contain a compound represented by the following Chemical Formula 3.
Chemical Formula
[0055] The negative electrode active material may include at least one selected from the group consisting of SiO a1 (0 < a1 ≦ 2), SiC a2 (0 < a2 ≦ 2), lithium-containing titanium composite oxide (LTO), artificial graphite, and natural graphite.
[0056] The lithium-containing titanium composite oxide is Li 4 Ti 5 O 12 , Li 0.8 Ti 2.2 O 4 , Li 8 Ti 4 O 12 and LiTi2 O 4 The present invention may include at least one selected from the group consisting of:
[0057] The negative electrode may be prepared by coating a negative electrode current collector with a negative electrode slurry including a negative electrode active material, a second internal solid electrolyte, a binder, a conductive material, a dispersant, a solvent, etc. Specifically, the negative electrode active material, the second internal solid electrolyte, the binder, the conductive material, and the dispersant are dispersed in a solvent to prepare a negative electrode forming slurry, which is then applied onto the negative electrode current collector and dried to prepare the negative electrode.
[0058] The binder, conductive material, dispersant, and solvent may be the same as those in the method for producing the positive electrode.
[0059] The negative electrode current collector may be made of, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like, or an aluminum-cadmium alloy.
[0060] The application and drying of the slurry may be performed in the same manner as in the method for manufacturing the positive electrode.
[0061] The step of forming the negative electrode laminate part may include a step of coating a slurry for forming a second external solid electrolyte layer, the slurry including a second external solid electrolyte, a binder, and a dispersant, on at least one surface of the negative electrode, and drying the slurry. Specifically, the second external solid electrolyte, the binder, and the dispersant may be dispersed in a solvent to prepare a slurry for forming the negative electrode laminate part, and the slurry may be coated on at least one surface of the negative electrode, and dried.
[0062] The binder, dispersant, and solvent may be the same as those described in the method for manufacturing a negative electrode.
[0063] The coating and drying of the slurry for forming the second outer solid electrolyte layer may be performed in the same manner as in the step of forming the positive electrode lamination part.
[0064] After forming a positive electrode laminate part and a negative electrode laminate part on the positive electrode and the negative electrode, respectively, a rolling step is performed in which the first outer solid electrolyte layer of the positive electrode laminate part and the second outer solid electrolyte layer of the negative electrode laminate part are brought into contact with each other so as to face each other.
[0065] The rolling may be carried out at a pressure of from 100 to 600 MPa, preferably from 200 to 550 MPa, more preferably from 400 to 500 MPa.
[0066] The rolling may be carried out by a known method such as compaction, roll press, isostatic compaction, or the like.
[0067] In this manner, a positive electrode having a positive electrode laminate portion formed thereon and a negative electrode having a negative electrode laminate portion formed thereon are separately manufactured, and then the positive electrode laminate portion and the negative electrode laminate portion are rolled so that they face each other and come into contact with each other. In this way, in the all-solid-state battery according to the present invention, physical detachment between each electrode and each external solid electrolyte layer can be suppressed despite an external impact or a volume change of the electrode that occurs during charging and discharging.
[0068] In particular, the first and second external solid electrolyte layers are formed in the form of thin films on the positive and negative electrodes, respectively, and are laminated and rolled so that the electrolyte layers are in contact with each other and face each other, so that the components of the solid electrolyte layers having different chemical compositions are not mixed with each other and each solid electrolyte layer can maintain its own chemical composition independently, thereby ensuring electrochemical stability at the interface between each external solid electrolyte layer and the electrode. Specifically, when the first external solid electrolyte layer is formed on the positive electrode and the second external solid electrolyte layer is formed on the negative electrode, the positive electrode slurry and the negative electrode slurry are adhered to the positive electrode and the negative electrode, respectively, via the binder during drying, thereby preventing physical detachment.
[0069] After the rolling step, the first outer solid electrolyte layer of the positive electrode lamination part and the second outer solid electrolyte layer of the negative electrode lamination part may be in separable contact with each other.
[0070] The first outer solid electrolyte layer of the positive electrode lamination part and the second outer solid electrolyte layer of the negative electrode lamination part include sulfide-based solid electrolytes having different chemical compositions, and in this case, the sulfide-based solid electrolyte may include a compound having an agyrodite crystal structure. EXAMPLES
[0071] The present invention will be described in more detail with reference to the following examples. However, these examples are merely intended to aid in the understanding of the present invention, and are not intended to limit the scope of the present invention in any way.
[0072] <Example 1> Production of all-solid-state battery 1 The solid electrolyte contained in the positive electrode (first internal solid electrolyte) is Li 6 P.S. 5 Cl, LiNi as positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 Carbon black was used as the conductive material and butadiene rubber was used as the binder. These were mixed with o-xylene as a solvent to produce a slurry for forming the positive electrode. This was then applied to aluminum foil as the positive electrode current collector using a doctor blade and dried at 120°C for 10 minutes.
[0073] Next, Li was placed on the positive electrode as the solid electrolyte (first external solid electrolyte). 6 P.S. 5 Cl and butadiene rubber as a binder were mixed with o-xylene as a solvent, and then the mixture was applied onto the positive electrode and dried at 120° C. for 10 minutes to form a positive electrode laminate on the positive electrode. The positive electrode laminate was then vacuum dried at 120° C. for 4 hours.
[0074] On the other hand, the solid electrolyte contained in the negative electrode (second internal solid electrolyte) is Li 5.4 P.S. 4.4 Cl 1.6A silicon-graphite composite was used as the negative electrode active material and butadiene rubber was used as the binder. These were mixed with o-xylene as a solvent to produce a slurry for forming the negative electrode. This was then applied to nickel foil as the negative electrode current collector using a doctor blade and dried at 120°C for 10 minutes.
[0075] Next, Li was placed on the negative electrode as the solid electrolyte (second external solid electrolyte). 5.4 P.S. 4.4 Cl 1.6 The mixture was then applied to the negative electrode and dried at 120° C. for 10 minutes to form a negative electrode laminate on the negative electrode. The negative electrode laminate was then vacuum dried at 120° C. for 4 hours.
[0076] The negative electrode having the negative electrode laminated portion formed thereon was arranged so that the negative electrode laminated portion faced upward, and the positive electrode having the positive electrode laminated portion was laminated on the negative electrode laminated portion so that the positive electrode laminated portion faced the negative electrode laminated portion. Then, the laminate was rolled at 90° C. and 450 MPa using a warm isotactic press to manufacture an all-solid-state battery.
[0077] <Example 2> Production of all-solid-state battery 2 Li as the first external solid electrolyte in the positive electrode laminate 6 P.S. 5 Li instead of Cl 5.4 P.S. 4.4 Cl 1.6 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the above-mentioned step was applied.
[0078] <Example 3> Production of all-solid-state battery 3 Li in the positive electrode lamination 6 P.S. 5 Li instead of Cl 5.7 P.S. 4.7 Cl 1.3 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the above-mentioned step was applied.
[0079] <Comparative Example 1> Production of all-solid-state battery 4 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the positive electrode lamination part did not include the first external solid electrolyte.
[0080] <Experimental Example 1> Evaluation of charge / discharge performance of all-solid-state batteries To evaluate the charge / discharge performance of the all-solid-state batteries, the all-solid-state batteries according to Examples 1 to 3 and Comparative Example 1 were charged and discharged once at 30° C. at a 0.05 C-rate, and the resulting voltage profiles are shown in FIG 3 and Table 1 below. The resistance values were calculated by discharging at 0.33 C for 10 seconds at a 50% state of charge (DC-IR).
[0081] [Table 1]
[0082] As a result of the experiment, it was confirmed that the all-solid-state batteries according to Examples 1 to 3, which use a positive electrode having a first external solid electrolyte layer formed thereon, have excellent charge capacity, discharge capacity, and average discharge voltage, as well as a low resistance value, compared to the all-solid-state battery according to Comparative Example 1, which does not have a first external solid electrolyte layer separately formed on the positive electrode. This is presumably because the first external solid electrolyte layer formed on one side of the positive electrode and the second external solid electrolyte layer formed on one side of the negative electrode maintain close contact between the positive electrode and the negative electrode, respectively, even during charging and discharging.
[0083] Meanwhile, comparing Example 1 with Examples 2 and 3, the effect of the type of the first outer solid electrolyte applied to the positive electrode can be confirmed. Specifically, the first outer solid electrolyte layer formed on one side of the positive electrode is Li 6 P.S. 5 In the case of Example 1 where Cl was applied, Li 5.4 P.S. 4.4 Cl 1.6 Or Li 5.7 P.S. 4.7 Cl 1.3 In other words, in all of Examples 1 to 3, the second external solid electrolyte formed on one side of the negative electrode was Li. 5.4P.S. 4.4 Cl 1.6 Considering that it is a common application of Li 6 P.S. 5 It was confirmed that the all-solid-state battery exhibits the best performance when the first external solid electrolyte layer of Cl is in face-to-face contact with the positive electrode. This is because the interface with the positive electrode is dominated by Li. 6 P.S. 5 The oxidation stability of Cl is improved by Li at the interface with the negative electrode. 5.4 P.S. 4.4 Cl 1.6 This is due to the excellent reduction stability of the material.
[0084] <Experimental Example 2> Evaluation of life characteristics of all-solid-state batteries In order to evaluate the life characteristics of the all-solid-state battery, the capacity during the cycle of the all-solid-state batteries according to Examples 1 to 3 and Comparative Example 1 was measured and shown in Table 2 below, and the capacity retention rate according to the cycle progression is shown in Figure 4. The initial charge / discharge was at 0.1 C-rate, and thereafter, charge / discharge was carried out at a rate-determining rate of 0.2 C-rate.
[0085] [Table 2]
[0086] The all-solid-state battery according to Example 1 maintained about 90% of the initial capacity (capacity at the second cycle) even after 50 cycles, and had a superior capacity retention rate even after repeated charging and discharging several times, compared to the all-solid-state battery according to Comparative Example 1. Moreover, the all-solid-state battery according to Example 1 showed a superior capacity retention rate compared to the all-solid-state batteries according to Examples 2 and 3.
[0087] That is, the Li formed on the positive electrode 6 P.S. 5 The solid electrolyte layer of Cl and Li formed on the negative electrode 5.4 P.S. 4.4 Cl 1.6 In the case of a laminated solid-state battery in which the solid electrolyte layers of the positive electrode and the positive electrode are in contact with each other, the solid electrolyte layer is not formed on the positive electrode or the Li 5.4 P.S.4.4 Cl 1.6 Or Li 5.7 P.S. 4.7 Cl 1.3 It was confirmed that the capacity retention rate was more excellent than that of the case where a solid electrolyte layer was formed.
[0088] On the other hand, in the case of Example 1, the highest capacity ratio was observed at a rate limiting rate of 0.2 C-rate compared to a rate limiting rate of 0.05 C-rate. This result shows that the expression of capacity at such a high rate is also associated with the low resistance value mentioned above.
Claims
1. a positive electrode laminate including a positive electrode and a first outer solid electrolyte layer formed on at least one surface of the positive electrode; and a negative electrode stacking portion including a negative electrode and a second external solid electrolyte layer formed on at least one surface of the negative electrode; Including, the first external solid electrolyte layer of the positive electrode laminate portion and the second external solid electrolyte layer of the negative electrode laminate portion face each other and are in contact with each other, The first outer solid electrolyte layer and the second outer solid electrolyte layer include sulfide-based solid electrolytes having different chemical compositions.
2. 2. The all-solid-state battery according to claim 1, wherein the first external solid electrolyte layer of the positive electrode laminate portion and the second external solid electrolyte layer of the negative electrode laminate portion are in contact with each other so as not to be mixed with each other and not to be physically separated from each other.
3. 2. The all-solid-state battery according to claim 1, wherein the sulfide-based solid electrolyte includes a compound having an agyrodite crystal structure.
4. The all-solid-state battery according to claim 1 , wherein the positive electrode comprises a positive electrode active material and a first internal solid electrolyte.
5. The all-solid-state battery according to claim 1 , wherein the negative electrode comprises a negative electrode active material and a second internal solid electrolyte.
6. The all-solid-state battery according to claim 4 , wherein the first internal solid electrolyte and the first external solid electrolyte each independently include a compound represented by the following Chemical Formula 1: 【Chemistry 1】 (In the above Chemical Formula 1, M 1 is at least one selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and mixtures thereof; M 2 is at least one selected from the group consisting of P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi, and mixtures thereof; M 3 is S, O or a mixture thereof, X is one or more elements selected from the Group 17 elements; -1≦a<0.3, -0.2≦b≦0.)
7. The all-solid-state battery according to claim 5 , wherein the second internal solid electrolyte and the second external solid electrolyte each independently include a compound represented by the following Chemical Formula 2: 【Chemistry 2】 (In the above Chemical Formula 2, M 1 is at least one selected from the group consisting of Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, and mixtures thereof; M 2 is at least one selected from the group consisting of P, N, Al, Si, Ga, Ge, As, In, Sn, Sb, Pb, Bi, and mixtures thereof; M 3 is S, O or a mixture thereof, X is one or more elements selected from the Group 17 elements; 0.3≦c≦1, −0.2≦d≦0.2.)
8. The all-solid-state battery according to claim 4 , wherein the positive electrode active material comprises a compound represented by the following chemical formula 3: 【Chemistry 3】 (In the above Chemical Formula 3, -0.05≦e≦0.2, 2≦f≦2.02, 0≦x≦1, 0≦y≦0.5, 0≦z≦0.5, and x+y+z=1; M 4 , M. 5 and M. 6 is at least one selected from the group consisting of Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga, and B.
9. The negative electrode active material is SiO a1 (0<a1≦2), SiC a2 6. The all-solid-state battery according to claim 5, comprising at least one selected from the group consisting of (0<a2≦2), lithium-containing titanium composite oxide (LTO), artificial graphite, and natural graphite.
10. forming a positive electrode laminate having a first outer solid electrolyte layer disposed on at least one surface of a positive electrode; forming a negative electrode laminate having a second outer solid electrolyte layer disposed on at least one surface of the negative electrode; and contacting the first external solid electrolyte layer of the positive electrode laminate portion and the second external solid electrolyte layer of the negative electrode laminate portion so as to face each other, and rolling the same; Including, The first outer solid electrolyte layer and the second outer solid electrolyte layer include sulfide-based solid electrolytes having different chemical compositions.
11. 11. The method for producing an all-solid-state battery according to claim 10, wherein after the rolling step, the first external solid electrolyte layer of the positive electrode lamination part and the second external solid electrolyte layer of the negative electrode lamination part are in contact with each other so as not to be mixed with each other and not to be physically separated from each other.
12. The method for producing an all-solid-state battery according to claim 10, wherein the sulfide-based solid electrolyte includes a compound having an agyrodite crystal structure.
13. The method for producing an all-solid-state battery according to claim 10 , wherein the positive electrode comprises a positive electrode active material and a first internal solid electrolyte.
14. The method for producing an all-solid-state battery according to claim 10 , wherein the negative electrode comprises a negative electrode active material and a second internal solid electrolyte.
15. 11. The method for manufacturing an all-solid-state battery according to claim 10, wherein the forming of the positive electrode lamination part comprises: applying a slurry for forming a first outer solid electrolyte layer, the slurry including a first outer solid electrolyte, a binder, and a dispersant, to at least one surface of the positive electrode, and drying the slurry.
16. 11. The method of claim 10, wherein the forming the negative electrode lamination part comprises: applying a slurry for forming a second outer solid electrolyte layer, the slurry including a second outer solid electrolyte, a binder, and a dispersant, to at least one surface of the negative electrode, and drying the slurry.
17. The method for producing an all-solid-state battery according to claim 15 or 16, wherein the drying is performed at 50°C to 150°C.
18. The method for producing an all-solid-state battery according to claim 10 , wherein the rolling is performed at a pressure of 100 to 600 MPa.